Evaluation of Maxillary Protraction Using a Mini Screw-Retained Palatal C-Shaped Plate and Face Mask - Mohamed Abdallah Elsaharty; Safaa Ali Ghobashi; Eman El-Shorbagy (Galenos Yayinevi, 2024)
Objective: To evaluate a newly designed minimally invasive palatal-plate face mask combination for the management of developing Class III malocclusion due to maxillary deficiency. Methods: A sample of 16 Class III patients due to maxillary deficiency in the early mixed dentition (8 boys and 8 girls) aged between 7 and 9 years participated in this study and were treated with a combination of palatal plate face masks. Extra-oral elastics were attached between the intra-oral and extra-oral appliances; the elastics were set at 30° to the occlusal plane. The force magnitude was 250-300 g per quadrant. Cephalometric radiographs were taken before and immediately after maxillary protraction. In addition, skeletal measurements were measured, tabulated, and statistically analyzed. The pre- and post-protraction measurements were compared using the Student's t-test, and the significance level was set at a p-value <0.05. Results: A statistically significant increase in SNA angle and maxillary length was observed by 3.13±1.52 degrees and 2.60±0.75 mm (p<0.05), respectively, indicating forward maxillary growth. The skeletal and soft tissue patterns were also improved, as evidenced by the statistically significant increase in the ANB angle, Wits appraisal, and H angle by 4.50±1.28 degrees, 5.30±1.86 mm, and 5.02±3.24 degrees (p<0.05), respectively. A favorable clockwise mandibular rotation was observed as evidenced by the increase in the SN/MP angle and the decrease in the SNB angle by 1.46±1.96 degrees and -1.38±1.86 degrees (p<0.05), respectively. Conclusion: The palatal-plate facemask combination is an effective treatment alternative for Class III malocclusion due to maxillary deficiency with minimal pain and discomfort.